2019
DOI: 10.1002/slct.201902151
|View full text |Cite
|
Sign up to set email alerts
|

A Bispyrazole Based Porous 2D Luminescent MOF for the Turn‐Off Detection of Pd(II) Ions

Abstract: A novel bispyrazole based porous MOF ({[Zn(MBPz)(Ene)0.5]⋅2DMF⋅2H2O}n (1)) with open alkene (‐HC=CH‐) and nitrogen sites has been synthesized, as an efficient fluorescent sensor for Pd(II) ions. The MOF exhibits 3D supramolecular structure with open channels having 27.2% porosity. The unsaturated ‐CH=CH‐ moieties are present along the walls of open channels which is favorable for interaction with guest moieties. The cation sensitivity of 1 was evaluated using a series of transition metal ions in DMF. The fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Recent studies have demonstrated that nanostructures made up of copper (Cu), cuprous oxide (Cu 2 O), and cupric oxide (CuO) have significant catalytic activity, comparable to or even greater than that of noble metals [108–114] . However, metal nanoparticle agglomeration through a reaction typically results in quick loss of catalytic properties, and recycling these small catalysts via repeated centrifuging and cleaning is a tedious and unsatisfactory technique [115–117] . Unfortunately, these Cu‐based catalysts still have robustness and recycling difficulties, so it is essential to design highly active NCs or nanocatalysts that are resistant to agglomeration and can be regenerated without complexity.…”
Section: Copper Ncsmentioning
confidence: 99%
“…Recent studies have demonstrated that nanostructures made up of copper (Cu), cuprous oxide (Cu 2 O), and cupric oxide (CuO) have significant catalytic activity, comparable to or even greater than that of noble metals [108–114] . However, metal nanoparticle agglomeration through a reaction typically results in quick loss of catalytic properties, and recycling these small catalysts via repeated centrifuging and cleaning is a tedious and unsatisfactory technique [115–117] . Unfortunately, these Cu‐based catalysts still have robustness and recycling difficulties, so it is essential to design highly active NCs or nanocatalysts that are resistant to agglomeration and can be regenerated without complexity.…”
Section: Copper Ncsmentioning
confidence: 99%
“…Using MOFs as catalysts not only improves their catalytic capabilities but also imbues them with certain electrical properties [24,25] . Shifting from homogeneous catalysis to heterogeneous catalysis is seen as a favourable course of action for environmentally sustainable and enduring advancements in the chemical industry [26–28] and catalysis [29] . The utilization of heterogeneous catalysts is highly preferred for organic reactions due to the drawbacks associated with traditional homogeneous catalysts including challenges in isolating the catalysts and managing the disposal and recovery of used catalysts [30–33] .…”
Section: Introductionmentioning
confidence: 99%